Global Shifts Business, Politics, and Deforestation in a Changing World Economy - Schleifer, Philip (Earth System Governance, 2023)
What global shifts in markets and power mean for the politics and governance of sustainability.In recent years, major shifts in global markets from North to South have created a new geography of trade and consumption, particularly in the agricultural sector. How this shift affects the governance of sustainability, and thus the future of the planet, is the pressing topic Philip Schleifer takes up in this book. The processes of twenty-first-century globalization are fundamentally changing the politics and governance of commodity production, Schleifer argues, with profound implications for the environment in the food-producing countries of the Global South. At the center of Schleifer's study are Brazil and Indonesia-two key sites of experimentation in new models of global environmental and commodity governance-where palm oil and soy supply chains have seen unprecedented degrees of private environmental governance in recent years. However, instead of transforming these industries, the diffusion of transnational sustainability standards has accompanied a worsening ecological crisis, with mounting evidence of increasingly strong links between deforestation and globalization in twenty-first-century agricultural trade. To uncover the causes of this governance failure, Schleifer develops a multi-level framework for analyzing how contemporary globalization is reconfiguring the political economies of such industries. The result is the first comprehensive analysis of the shift of global agricultural trade to the South and the deepening crisis of commodity-driven deforestation-and a complex and evolving picture of both the risks and opportunities for sustainability presented by this transformative shift.